الحل القضائي في محكمة العدل الأوروبية واسباب فعاليته في حل النزاعات الدولية - بورنان, منال (University of Eloued جامعة الوادي, 2020)
لكي تفرض المنظمات الإقليمية الدولية فاعليتها في المجتمع الدولي ضمنت مواثيقها بنظم أساسية لأجهزة قضائية تتولى حل النزاعات التي تنشأ بين الدول الأعضاء فيها وهذا ساعد على الكشف عن العديد من قواعد القانون الدولي. وتعتبر محكمة العدل الأوروبية للاتحاد الأوروبي جهاز قضائي نشيط وفعال في مجال التسوية القضائية للنزاعات الدولية وذلك راجع لفتح مجال حق المثول امامها لكافة الأشخاص الدولية المعنوية منها أو الطبيعية هذا من جهة، ومن جهة اخرى ضمنت اتخاذ كافة الإجراءات الضرورية لمتابعة تنفيذ الحكم الصادر عنها في الواقع بالاعتماد على الوسائل التي تتبع لتنفيذ الأحكام القضائية الصادرة عن القضاء الوطني. وأيضا اتباع قواعد القضاء الوطني فيما يتعلق بطرق الطعن من دعاوى الإلغاء ودعاوى القضاء الكامل إلى النقض والاستئناف. وتؤكد الممارسة الدولية عل العموم احترام الدول الأعضاء للأحكام الصادرة عن محكمة عدل المجموعات الأوروبية وتنفيذها فورا إلا إذا تطلب الأمر اتخاذ إجراءات داخلية.In order to enhance its performance and effectiveness in the international society, international & regional organizations equipped their judicial organ’s charters with systems to take in hand the international disputes.settlement between or among member states. Which helped to unveil -in the process- many new international laws. From this perspective, the European Court of Justice of the European Union is considered an active & effective judicial organ in the judicial settlement of international disputes, by giving every international legal personality the right to appear before it on one hand. On the other hand, it ensures that all necessary measures are taken to follow up the implementation of issued judgments & decisions, by using – among others- every domestic legal means that lead to the implementation of these decisions. The international practice -in general- tends to confirm the compliance with the European Court of Justice’s decisions from all its members. Furthermore, its immediate implementation, except for the cases where it has no jurisdiction (where domestic actions are required.
مقال
Keywords: الاحكام الدولية ; الاتحاد الاوروبي ; محكمة العدل للاتحاد الاوروبي; European; Court; Justice; International; judgments; organizations; disputes; Permanent